A novel gene (FAM20B encoding glycosaminoglycan xylosylkinase) for neonatal short limb dysplasia resembling Desbuquois dysplasia. Issue 6 (11th April 2019) - Kuroda, Yukiko; Murakami, Hiroaki; Enomoto, Yumi; Tsurusaki, Yoshinori; Takahashi, Kazumi; Mitsuzuka, Kanako; Ishimoto, Hitoshi; Nishimura, Gen; Kurosawa, Kenji
Abstract : Desbuquois dysplasia (DBQD) is an autosomal recessive heterogeneous disorder characterized by joint laxity and skeletal changes, including a distinctive monkey‐wrench appearance of the femora, advanced carpal ossification, and abnormal patterning of the preaxial digits. Two genes for DBQD ( CANT1 encoding calcium‐activated nucleotidase‐1 and XYLT1 encoding xylosyltransferase‐1) have been reported. We propose a novel gene for neonatal short limb dysplasia resembling DBQD, based on the phenotype and genotype of two affected siblings. The affected boy and girl died in early infancy and shortly after birth, respectively. The clinical hallmarks included mid‐face hypoplasia, thoracic hypoplasia with respiratory failure, very short stature (approximately −7 SD of birth length) with mesomelic shortening of the limbs, and multiple dislocations of the large joints. Radiological examinations showed prominent lesser trochanter, flared metaphyses of the long bones, and joint dislocations. The affected boy had preaxial digital hypoplasia, and the affected girl showed overlapping and syndactyly of the preaxial digits. Molecular analyses of the girl showed compound heterozygous variants in FAM20B (NM_014864: c.174_178delTACCT p.T59Afs*19/c.1038delG p.N347Mfs*4). FAM20B encodes glycosaminoglycan xylosylkinase, which acts downstream of xylosyltransferase‐1. Given the fact that FAM20B deficiency causes skeletal phenotypes in mice and zebrafish, these variants are highly probable to be pathogenic. Abstract :